Biomechanical insights through finite element analysis of Bennett fracture fixation: a comparative study of four surgical techniques - Numan Mercan; Ebubekir Eravşar; Selim Safalı; Levent Uğur; Ali Özdemir (Journal of Orthopaedic Surgery and Research)
Abstract Background and objectives Bennett fractures are intra-articular fractures of the first metacarpal, typically resulting from axial loading. The optimal surgical method for fixation remains a topic of ongoing debate. This study aims to evaluate and compare the biomechanical properties of different fixation techniques. Materials and methods Four fixation models were analyzed: the Lag Screw (LS) model, the Plate-screw (PS) model, and two K-wire models (Kw1 and Kw2). The biomechanical stability of each model was assessed by measuring the total displacement at the fracture line and the maximum von Mises stresses (MvMs) on the fixation materials. Results Measurements revealed that the LS model exhibited the highest total displacement of 2,184 mm, while the PS model showed the least displacement at 0,069 mm. Among the K-wire models, Kw1 had a total displacement of 0,408 mm, while Kw2 displayed 0,146 mm. Notably, the MvMs values at the fracture line were highest in the LS model (623,95 MPa for the large fragment surface) and lowest in the Kw2 model (16,237 MPa). The PS model demonstrated the lowest stresses on the fixation materials, highlighting its biomechanical advantage. Furthermore, the assessment of joint-level displacement indicated that the Kw1 model had the greatest displacement (0,156 mm), while the PS model maintained remarkable stability, recording a stable 0 mm displacement. Conclusion The PS model demonstrated superior biomechanical stability, making it the most suitable fixation method among those studied. While the Kw2 model showed promising results with low total displacement values, further studies are necessary to establish its clinical efficacy.